In Vivo Anti-Inflammation Potential of Aster koraiensis Extract for Dry Eye Syndrome by the Protection of Ocular Surface - Hong, Sung-Chul; Ha, Jung-Heun; Lee, Jennifer K.; Jung, Sang Hoon; Kim, Jin-Chul (MDPI, 2020)
Dry eye syndrome (DES) is a corneal disease often characterized by an irritating, itching feeling in the eyes and light sensitivity. Inflammation and endoplasmic reticulum (ER) stress may play a crucial role in the pathogenesis of DES, although the underlying mechanism remains elusive. Aster koraiensis has been used traditionally as an edible herb in Korea. It has been reported to have wound-healing and inhibitory effects against insulin resistance and inflammation. Here, we examined the inhibitory effects of inflammation and ER stress by A. koraiensis extract (AKE) in animal model and human retinal pigmented epithelial (ARPE-19) cells. Oral administration of AKE mitigated DE symptoms, including reduced corneal epithelial thickness, increased the gap between lacrimal gland tissues in experimental animals and decreased tear production. It also inhibited inflammatory responses in the corneal epithelium and lacrimal gland. Consequently, the activation of NF-kappa B was attenuated by the suppression of cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2). Moreover, AKE treatment ameliorated TNF-alpha-inducible ocular inflammation and thapsigargin (Tg)-inducible ER stress in animal model and human retinal pigmented epithelial (ARPE-19) cells. These results prove that AKE prevents detrimental functional and histological remodeling on the ocular surface and in the lacrimal gland through inhibition of inflammation and ER stress, suggesting its potential as functional food material for improvement of DES.
Keywords: ENDOPLASMIC-RETICULUM STRESS; ANTIOXIDANT ACTIVITY; TNF-ALPHA; KAPPA-B; DISEASE; MECHANISMS; EXPRESSION; PATHOPHYSIOLOGY; DISRUPTION; EPITHELIUM